GENDER INEQUALITY IN WOMEN LEADERSHIP OF PUBLIC SECTOR INSTITUTIONS IN PAPUA, INDONESIA - Titia Erika Sarlota Awom,; Maria Niester Insoraki Komboy, (International Journal of Social Science, 2025)
The gender inequality still exists in the workplace, where women face barriers to improving a higher career path. One of the barriers comes from the institutional environment in the form of gender gap, which make it increasingly difficult for women to reach leadership position. Gender stereotypes halt women’s career advancement, resulting in a glass ceiling phenomena. This study examines the effect of gender inequalities on career satisfaction towards Papuan women leadership during their employment among public institutions. Descriptive qualitative approach was used; the participants selected were female leaders in public institution including education, government, health, and libraries sector. Pattern across the study showed that women remain underrepresented in upper-level management position because they feel unfairly treated by the institution. Barriers generally outweigh opportunities for career advancement; these including glass ceiling phenomena in the workplace by asserting that men make better leaders. Consequently, more women are rising into leadership roles at all levels, including functional public service positions. Given these results, leaders need to build high quality relationship with employer and employee to prevent a glass ceiling in the workplace, resulting in promoting gender equity more broadly within the public whom they serve.